LEARNING CYCLE 5E MODEL EFFECT TO SENIOR HIGH SCHOOL STUDENT’S LEARNING COMPETENCIES - Brigita Mairosa; Ardi Ardi; Sa'diatul Fuadiyah; Armen Armen (Universitas Negeri Padang, 2021)
The problem at SMAN 5 Solok Selatan is the low level of student learning competencies which includes aspects of knowledge, attitudes, and skills. Efforts that can be done are applying the LC 5E learning model on ecological material at Solok Selatan 5 High School. This type of research is a semi-experimental research design, namely the Randomized Control-Group Posttest Only Design. The population in the study of all students of class X MIPA SMAN 5 Solok Selatan who were enrolled in the 2018/2019 Academic Year amounted to 111 people grouped in four classes. Sampling used purposive sampling technique, class X MIPA 2 as experimental class I and class X MIPA 1 as experimental class II (control). Instruments in the form of posttest questions for knowledge competencies, observation sheets for attitude competencies and product assessment for skills competencies. Based on the results of the study using the t-test on the competency of students' knowledge the value of tcount was 3.012>1.67 t table, and the competency skill was tcount 3.67>1.67 t table. In the attitude competence of the experimental class 83% are good categories while the control class is 72% with sufficient categories. This shows that the hypothesis is accepted in the competence of knowledge, attitudes and skills. The conclusion of the study is that the LC 5E learning model has a positive effect on students' learning competencies in ecological material at SMAN 5 Solok Selatan.